Design of a Branch-line Microstrip Coupler Using Spirals and Step Impedance Cells for WiMAX Applications - Hosseini, Sayed M.; Rezaei, Abbas (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
branch-line microstrip coupler is designed and fabricated in this paper. The proposed coupler operates at 3 GHz, which is suitable for WiMAX applications. The designed coupler has a high performance, that is, a low phase difference of 0.49°, low insertion loss, good coupling factor, and good isolation better than −30 dB. Another advantage of the designed coupler is its novel geometrical structure based on integrating the semi-circular and step impedance cells. The design process is based on introducing and analyzing an equivalent LC model to improve impedance matching and reduce losses. To verify the design process, the designed coupler is fabricated, where a good agreement between the simulation result and measurement is achieved.